TRANSFORMATION OF MUNICIPAL WASTE MANAGEMENT SYSTEMS IN THE CIRCULAR ECONOMY PARADIGM. EXPERIENCE OF UKRAINE - Khrutba, Yuliia; Goncharenko, Nataliia; Sorochynska, Olena (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The study analyzes the current state and trends in the development of the solid waste management system (SWMS) in Ukraine in the context of European integration and military challenges. The authors substantiate the need to transition from a linear consumption model to a circular economy paradigm, which involves minimizing waste generation, expanding recycling and reusing resources. Particular attention is paid to a comparative analysis of Ukrainian legislation with EU directives, in particular on the implementation of the waste management hierarchy and extended producer responsibility. The paper identifies key barriers to sustainable waste management in Ukraine: the lack of modern sorting infrastructure, low level of investment support and critical accumulation of waste in landfills. The practical significance of the study lies in the development of recommendations for the transformation of municipal waste management systems through the involvement of green financing, digitalization of monitoring and the introduction of innovative recycling technologies. The results of the study can be used by local governments to develop regional waste management plans that meet ESG principles and sustainable development goals.